PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE JD.ID BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Winner Daud Silaban (2021)
E-commerce has facilitated the traditional transaction style, namely direct interaction between consumers and business actors in a trading activity, where the concept has turned into a modern transaction, namely trading using internet or virtual media that does not need to have face-to-face meetings between consumers and business actors in activities. trading. Where every transaction activity is carried out online, from payment, ordering, advertising to delivery, it is also carried out using the internet. E-commerce transactions in their implementation, have advantages as well as disadvantages. The advantages are efficiency that can be felt directly where consumers can save costs and time and the freedom to choose the type of goods and services that suit their needs. However, the drawback is that because of these conditions, the position of consumers is weaker than the position of business actors which can cause losses and disappointments because consumers cannot see the products ordered directly and consumers are required to pay in advance so that consumers do not have a guarantee that the products ordered arrive at the customer. destination, arrived on time according to the invoice, quality product or in accordance with what you are looking for. Therefore, consumer protection is needed to ensure a sense of security and comfort in transactions.